Uji Beberapa Pupuk Organik Terhadap Pertumbuhan dan Produksi Okra (Abelmoschus Esculantus) Pada Tanah Inseptisol - Marisa Marisa; Zulfatri Zulfatri; Al Ichsan Amri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
Okra is a vegetable plant the has long been cultivated in Indonesia. Okra can growth on soils low fertility, such as inceptisol soils. This research was aimed to obtain the best type of organic fertilizer in improving the growth and production of grow in Inceptisol. This research was conducted at Agricultural Faculty of Universitas of Riau in October-December 2018. The provision of organic matter (P) consisting of P0 = without applying organic P1 organic fertilizer = Vermikompos 15 t. ha-1 (3kg/plot) P2 = Cow Manure 15 t. ha-1 (3kg/plot) P3 = egg shell flour 15 t. ha-1 (3kg/plot) P4 = TKKS of 15 t. ha-1 (3kg/plot). The observed parameters are the height of the plant, the number of leaves, circular stem, flowering age, harvest age, the number of crop samples and the weight of cropping samples. The Data obtained was analyzed in a statistiling and advanced tests of Duncan New Multiple Range Test (DNMRT) at a 5% level. The results showed that some organic fertilizers such as vermicompost, cow dung, eggshell fertilizer and TKKS compost were more influential than not being given organic fertilizer. The best fertilizer in this research is cow manure that giving the best result on growth and production of okra compared to other fertilizers. Keywords: okra, vermicompos, cow manure, egg shell flour, fertilizer TKKS